Modulation of acute coronavirus-induced encephalomyelitis in γ-irradiated rats by transfer of naive lymphocyte subsets before infection - Schwender, Stefan; Hein, Andreas; Imrich, Horst; Czub, Stefanie; Dörries, Rüdiger (Journal of neurovirology, 1999)
Clinical course, recovery of infectious virus from brain tissue and histopathology of the central nervous system were examined in γ-irradiated Lewis rats reconstituted by naive lymphocytes before infection with coronavirus MHV-4 (strain JHM). Up to 9 days past infection, no differences were seen between immunologically competent and immuno-deficient animals in terms of onset and progression of neurological disease. However, in the latter animals neurological symptoms were dominated by signs of encephalitis instead of paralytic disease as usually seen in immunocompetent animals. Nevertheless, despite high titers of infectious virus in the CNS of immunodeficient animals only mild histopathological changes were noticeable. In contrast, infectious virus in the CNS of immunologically competent animals was below the detection limit of the assay. Paralytic disease and tissue destruction were T lymphocyte mediated because γ-irradiated rats that were reconstituted by CD4+ or CD8+ T lymphocyte enriched cells in the absence of B lymphocytes revealed an earlier onset of clinical symptoms and a more rapid deterioration of their clinical state compared to fully competent animals. Whereas in CD4+ T cell reconsituted animals infectious virus was moderately reduced and tissue destruction as well as inflammatory changes in the CNS were focal, in CD8+ T cell reconstituted animals vacuolizing white matter inflammation was diffuse without reduction of infectious virus in brain tissue. From the presented data we conclude that in the acute stage of JHMV-induced encephalomyelitis of Lewis rats: (i) tissue destruction and paralytic clinical symptomatology are mainly T cell-mediated; (ii) CD4+ T lymphocytes can directly contribute to reduction of viral load in the brain and (iii) only coordinated action of both, the T and the B cell compartment enables animals to survive the infection and recover from disease.
Elektronische Reproduktion der Druck-Ausgabe
Published online: 10 Jul 2009
Gesehen am 30.06.2022